Pedagogical Bioethics Initiatives - M. S. Gorbuleva; I. V. Melik-Gaykazyan; N. A. Pervushina (Высшее образование в России)
The peculiarity of bioethics is the development of such invariant principles and rules that allow predictable variational interpretation depending on specific axiological and communicative formats of situations. The noted semiotic peculiarity is updated in connection with the project of collaboration of various universities within one region. The authors consider the success of the project in satisfying the request for the training of unique specialists. In this regard, the authors interpret the pedagogical bioethics as the training of self-defense of the individuality and as education of the desire to acquire unique experience. The authors present the directions of pedagogical bioethics, which enable: (1) to overcome the standardization of personality; (2) to become consulting for the formation of individual educational trajectories; (3) to perform the function of informed consent in the context of the implementation of innovative educational technologies based on the achievements of neurophysiology and cognitive sciences; (4) in the context of university integration, to play the role of a dominant of education in the humanities to overcome “moral color vision deficiency”. The listed initiatives of pedagogical bioethics are put forward on the base of the results of the research in the field of visual semiotics.